SDG5 "Gender Equality" and the COVID-19 pandemic: A rapid assessment of health system responses in selected upper-middle and high-income countries - Ellen Kuhlmann; Gabriela Lotta; Gabriela Lotta; Michelle Fernandez; Asha Herten-Crabb; Leonie Mac Fehr; Jaimie-Lee Maple; Ligia Paina; Clare Wenham; Karen Willis (Frontiers Media S.A., 2023)
IntroductionThe COVID-19 pandemic disrupted healthcare and societies, exacerbating existing inequalities for women and girls across every sphere. Our study explores health system responses to gender equality goals during the COVID-19 pandemic and inclusion in future policies.MethodsWe apply a qualitative comparative approach, drawing on secondary sources and expert information; the data was collected from March-July 2022. Australia, Brazil, Germany, the United Kingdom, and the USA were selected, reflecting upper-middle and high-income countries with established public health and gender policies but different types of healthcare systems and epidemiological and geo-political conditions. Three sub-goals of SDG5 were analyzed: maternity care/reproductive health, gender-based violence, and gender equality/women's leadership.ResultsWe found similar trends across countries. Pandemic policies strongly cut into women's health, constrained prevention and support services, and weakened reproductive rights, while essential maternity care services were kept open. Intersecting gender inequalities were reinforced, sexual violence increased and women's leadership was weak. All healthcare systems failed to protect women's health and essential public health targets. Yet there were relevant differences in the responses to increased violence and reproductive rights, ranging from some support measures in Australia to an abortion ban in the US.ConclusionsOur study highlights a need for revising pandemic policies through a feminist lens.